Efektivitas Jaminan Sosial (BPJS Kesehatan) bagi Masyarakat Miskin di Desa Rambigundam Kecamatan Rambipuji Kabupaten Jember - Tioma R. Hariandja; Suphia Suphia (JURNAL RECHTENS, 2019)
Jember district government, through the granting of the National Health Insurance -Indonesia Healthy Card (JKN-KIS) for the poor in an effort to implement universal healthcoverage (UHC). Rambigundam Village Rambipuji District as one of the villages in JemberRegency has also implemented the giving of the Healthy Indonesia Card (KIS) to the villagecommunity in accordance with the Bupati's Directive. Based on the Profile of DesaRambigundam that the availability of limited health services, the low interest of thecommunity to have higher education and the employment status of the community are mostlyfarm laborers and domestic workers. The implementation of the National Health Insuranceaccording to the laws is regulated in Presidential Regulation Number 12 of 2013 concerningHealth insurance. According to this regulation Article 1 number 3 Recipients of HealthAssistance Assistance (PBI) Health Insurance are poor and disadvantaged people are furtherregulated in Article 6 number 1 which states that membership in Health Insurance ismandatory and is carried out in stages.Keywords :Effectiveness, Social Security, Poor Socie